Alternativas Etológicas para el Control de Plagas en el Cultivo de Chocho (lupinus mutabilis sweet). Sector Plaza Arenas, Parroquia Pujili, Cantón Pujili, Provincia Cotopaxi 2017. - Chilig Pilicita, Katherine Yesseña (2017)
The research was based on the Ethological Control of pest in the chocho. With the following general objective "To evaluate the monochromatic traps and ethological baits for the control of pest in the cultivation of chocho (Lupinus mutabilis Sweet). Sector Plaza Arenas, Parish Pujili, Canton Pujili, Province Cotopaxi 2017 ". With the following methods: monochromatic traps yellow, monochromatic traps blue, toxic baits (bran plus molasses and Deltametrina 1%) and homemade bait (water plus detergent) the number of plots was 24 the same that were divided into 4 treatments And 6 replicates. A Full Random Blocks design was applied for this treatment. The efficiency of the project was measured based on the index of pests in the plot, proving which of the traps and baits have the highest insect capture, The identification of insects was carried out in which it was obtained that the largest number of insects found in the research is of the Order Diptera, Muscidae Family with a total of 16055 insects in all the phonological stages of the crop, having a higher incidence of population in the flowering stage with an average of 80.64% insects and the lowest average incidence of population are several families which are Scarabaeidae and Scollidae in the phonological stage of development of the plant, Apidae in the estate phonological of Prefloration y floriation, Empididae y Elateridae in la formation de pods, Elateridae in the maturation de pods con un promotion de 0.015 insects, the highest number of insects captured was in the monochromatic traps yellow , followed second by the monochrome traps blue , third followed by home bait and finally toxic bait with fewer insects captured , In the stage of Prefloration no catches of this family Muscidae was obtained and the amount of insects of the different families was reduced and at the time in each stage new families of insects appeared and In others he disappeared in a total of 4 orders and 18 Families At the same time data were taken on plant height with a coefficient of variation of 11.24%, number of branches with a coefficient of variation of 9.14%, number of pods per central axis with a coefficient of variation of 11.76% In which results and similar averages were obtained due to several factors that could influence in the capture of the insects and the development of the plant. In the economic analysis it was found that the best treatment was (Toxic bait) with a production of 157 kg with a value of 408.20 US with a cost benefit of 563.23US